1997
DOI: 10.1159/000027256
|View full text |Cite
|
Sign up to set email alerts
|

Cystatins in Tears of Patients with Different Corneal Conditions

Abstract: A presence of cystatins, inhibitors of cysteine protease, was investigated in tears of patients with different corneal pathologies. Tear fluid samples were collected with glass capillaries in 28 patients (28 eyes) and 15 healthy controls (15 eyes). Only after corneal transplantation (8) or in corneal dystrophy (6) but not after cataract extraction (5) or other traumatic conditions of the cornea (9) was a significant difference in inhibitory activity of cystatins measured in comparison with the 15 controls. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Cystatin S and SN are extracellular proteins and their role as proteinase inhibitors to prevent uncontrolled proteolysis and tissue damages is well established . It is suggested that low levels of cystatin S and SN might increase the level of tear protease and its activity, and their reduction is attributed to keratoconus, blepharitis and in reflex tearing as shown in this study .…”
Section: Discussionsupporting
confidence: 55%
“…Cystatin S and SN are extracellular proteins and their role as proteinase inhibitors to prevent uncontrolled proteolysis and tissue damages is well established . It is suggested that low levels of cystatin S and SN might increase the level of tear protease and its activity, and their reduction is attributed to keratoconus, blepharitis and in reflex tearing as shown in this study .…”
Section: Discussionsupporting
confidence: 55%
“…The three fold reduction of cystatins in the tears of patients with fungal keratitis correlates well with their functional role. Cysteine protease inhibitors are reduced in several pathological conditions [48].…”
Section: Discussionmentioning
confidence: 99%
“…Cystatins are low-molecularweight proteins that inhibit cysteine proteinases and were first discovered in chicken egg whites, but can be found in various body fluids, including tears [29,30]. A low level of cystatins in tears might harm the balance with cysteine proteases and lead to a higher risk of proteolytic attacks [31]. We have demonstrated that besides decreased levels of lysozyme in the group of soft contact lens wearers (CL_S), protein intensities of protective cystatins are also decreased in the soft contact lens group (CL_S).…”
Section: Discussionmentioning
confidence: 99%